Evaluation of US EPA Method 3052 Microwave Acid Digestion for Quantification of Majority Metals in Waste Printed Circuit Boards - Dagmar Remeteiová; Silvia Ružičková; Vladislava Mičková; Martina Laubertová; Róberta Slezáková (Metals, 2020)
Metal content determination is one of the critical aspects of preparing electronic waste for metal recycling. In spite of the fact that end-of-life printed circuit boards are considered to be a secondary resource reservoir, no standard procedure exists for determining the total metal content in this heterogeneous multicomponent material containing plastics, metals, alloys and ceramics. We investigated the utilization of United States Environmental Protection Agency (US EPA) microwave acid digestion (Method 3052) and various modifications of this procedure for effective releasing of Cu, Fe, Ni, Pb and Zn from waste printed circuit boards (WPCBs) from mobile phones. The maximum contents of Cu (22.6 wt.%), Fe (5.0 wt.%), Ni (2.0 wt.%) and Zn (2.6 wt.%) were obtained using the standard (unmodified) US EPA 3052 digestion procedure, but the total digestion of PCB material was not achieved. The solid residue material after digestion by means of the US EPA 3052 method consisted predominantly of oxides (Ca, Mg and Al) and fluorides (Ca and Mg), and some particles contained minor amounts of Fe and Cu.